2011
DOI: 10.2355/isijinternational.51.1316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Softening, Shrinking and Melting Reduction Behavior of Raw Materials for Blast Furnace

Abstract: To evaluate influences on the softening and melting behavior of blast furnace raw materials, the examinations of high temperature properties in various types of raw materials for blast furnaces were executed. Shrinking behavior before reaching approximately 1 300°C is estimated by using softening viscosity taking into consideration pores of particles, and void ratio as well as liquid phase ratio of the layer. The softening viscosity of the solid phase of approximately 10 10 Pa·s was obtained and the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 8 publications
0
41
0
Order By: Relevance
“…BF is conceptually divided into zones, according to the temperature, chemical reactions and the oxidation state of iron, such as lumpish zone and cohesive zone . The shape and position of the cohesive zone in blast furnace has a pronounce effect on the gas flow pattern, which in turn alters the efficiency and productivity of the blast furnace process . The high temperature properties of ferrous burden largely control the shape, width, and position of cohesive zone.…”
Section: Introductionmentioning
confidence: 99%
“…BF is conceptually divided into zones, according to the temperature, chemical reactions and the oxidation state of iron, such as lumpish zone and cohesive zone . The shape and position of the cohesive zone in blast furnace has a pronounce effect on the gas flow pattern, which in turn alters the efficiency and productivity of the blast furnace process . The high temperature properties of ferrous burden largely control the shape, width, and position of cohesive zone.…”
Section: Introductionmentioning
confidence: 99%
“…Another weakness is that some softening studies comprise only an individual pellet 16,17) or a couple of pellets 2,3,[9][10][11][12][13][14][15]18) instead of a packed bed of pellets. 7,8,[19][20][21][22][23][24][25][26][27][28][29][30] Studies 2,7,[21][22][23][24][25][26][27][28][29] have been carried out for iron ore pellets under load dynamically from ambient temperature to elevated temperatures using a simulated BF gas. Recently, Guha and Sinha 29) presented a modified softening-melting test with a possibility to use a gas composition varying with temperature/time to better simulate the actual conditions in a BF.…”
Section: Introductionmentioning
confidence: 99%
“…While, the high temperature properties of blast furnace slags play an important role on the softening and melting behavior of raw materials in blast furnace. 1,2) Many researchers have found that the chemical composition, such as CaO/SiO2, Al2O3 and MgO content, have great influence on the fluidity and viscosity of blast furnace slags. [3][4][5] On the other hand, researchers also found that the sinter of high basicity would interact with lump ores or pellets at high temperature, the softening and melting properties of lump ores or pellets would be improved by the high temperature interaction.…”
Section: Introductionmentioning
confidence: 99%